Parental Educational Attainment and Chronic Medical Conditions among American Youth; Minorities' Diminished Returns - Shervin Assari; Mohsen Bazargan; Cleopatra H. Caldwell (MDPI AG, 2019)
Background: Parental educational attainment is protective against chronic medical conditions (CMCs). According to the minorities' diminished returns (MDRs) theory, however, the health effects of socioeconomic status (SES) indicators are smaller for socially marginalized groups such as racial and ethnic minorities rather than Whites. Aims: To explore racial and ethnic differences in the effect of parental educational attainment on CMCs in a nationally representative sample of American youth. Methods: In this cross-sectional study, we used baseline data of 10,701 12-17 years old youth in the Population Assessment of Tobacco and Health (PATH; 2013). Parental educational attainment was the independent variable. The dependent variable was the number of CMCs in youth. Age, gender, and family structure were covariates. Race and ethnicity were the focal moderators. Linear and multinomial regression were applied to analyze the data. Results: Overall, higher parental educational attainment was associated with a lower number of CMCs. Race and ethnicity, however, showed significant interactions with parental educational attainment on a number of CMCs as well as 2+ CMCs, suggesting that the effect of parenting educational attainment on CMCs is significantly smaller for Black and Hispanic than White youth. Conclusions: In the United States, race and ethnicity alter the health gains that are expected to follow parental educational attainment. While White youth who are from highly educated families are most healthy, Black and Hispanic youth from highly educated families remain at higher risk for CMCs. That means, while the most socially privileged group, Whites, gain the most health from their parental education, Blacks and Hispanics, the least privileged groups, gain the least. The result is a disproportionately high number of CMCs in middle-class Blacks and Hispanics. Economic, social, public, and health policy makers should be aware that health disparities are not all due to lower SES of the disadvantaged group but also diminished returns of SES resources for them. Youth physical health disparities due to race and ethnicity exist across all SES levels.